NMR crystallography to probe the breathing effect of the MIL‐53(Al) metal–organic framework using solid‐state NMR measurements of 13C–27Al distances. Issue 3 (6th February 2017) - Giovine, Raynald; Volkringer, Christophe; Trébosc, Julien; Amoureux, Jean-Paul; Loiseau, Thierry; Lafon, Olivier; Pourpoint, Frédérique
Abstract : We show how 13 C– 27 Al solid‐state NMR experiments distinguish between the large and narrow pore structures of MIL‐53(Al). These experiments also prove the rigidity of these structures and provide an estimate of the average distance between the free ligand and the framework in the as‐synthesized MIL‐53(Al) material. Abstract : The metal–organic framework MIL‐53(Al) (aluminium terephthalate) exhibits a structural transition between two porous structures with large pore ( lp ) or narrow pore ( np ) configurations. This transition, called the breathing effect, is observed upon changes in temperature or external pressure, as well as with the adsorption of guest molecules, such as H2 O, within the pores. We show here how these different pore openings can be detected by observing the dephasing of 13 C magnetization under 13 C– 27 Al dipolar couplings using Rotational‐Echo Saturation‐Pulse Double‐Resonance (RESPDOR) solid‐state NMR experiments with Simultaneous Frequency and Amplitude Modulation (SFAM) recoupling. These double‐resonance NMR experiments between 13 C and 27 Al nuclei, which have close Larmor frequencies, are feasible thanks to the use of a frequency splitter. The experimental SFAM–RESPDOR signal fractions agree well with those simulated from the MIL‐53(Al)‐ lp and ‐ np crystal structures obtained from powder X‐ray diffraction analysis. Hence, these 13 C– 27 Al solid‐state NMR experiments validate these structures and confirm their rigidity. A similar agreement is reported for the framework ligands in the as‐synthesized ( as ) MIL‐53(Al), in which the pores contain free ligands. Furthermore, in this case, 13 C– 27 Al SFAM–RESPDOR experiments allow an estimation of the average distance between the free ligands and the 27 Al nuclei of the framework.